Correlation between Urine Albumin Creatinin Ratio (UACR) Value to Urine Osmolality Value and Estimate Glomerular Filtration Rate (EGFR) Value on Patient with Kidney Failure - Lisa Anis Fadilatin; Andika Aliviameita (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background : Kidney failure is one of the causes of death in the world. Laboratory tests related to kidney function are very important in the management of patients with kidney failure because they are useful in identifying any decline in kidney function, monitoring treatment and progression of kidney disease. The urine albumin creatinine ratio (UACR): is related to assess the protein filtration function in the glomerulus. The urine osmolality is to assess pre-renal, renal and post-renal hemodynamic status. The estimated glomerular filtration rate (EGFR) is to assess overall glomerular function. EGFR is the gold standard. The aim of this research is to determine 1). The correlation between UACR value to urine osmolality value, 2). The correlation between UACR value to EGFR value. Patient with kidney failure is the independent variable, meanwhile UACR value, urine osmolality value and EGFR value are dependent variables. Methods : This study is a quantitative study with analytical observations through a cross sectional design using 30 sample patients with kidney failure either acute kidney injury (AKI) or chronic kidney disease (CKD). This study was conducted from May to June 2024 at the Central Laboratory Installation of Dr. Saiful Anwar Hospital, East Java Province. UACR and EGFR examination used the principle of photometric test while urine osmolality examination used the principle of electrical conductivity. The data were analyzed using the Shapiro-Wilk normality test and the Spearman non-parametric correlation test through SPSS 27. Results : In the normality test results, it was found that UACR and EGFR values were not normally distributed (p = <0.001) while urine osmolality values were normally distributed (p = 0.523). Spearman's non-parametric correlation test showed that there was no correlation between UACR to urine osmolality (p = 0.342) and EGFR value (p = 0.481). Conclusion : The results of this study showed no correlation between UACR value to urine osmolality value and EGFR value in patients with kidney failure.